GPR35-mediated metabolic reprogramming promotes tumorigenesis in digestive cancers - Wang, Fang; Ding, Xin-Xin; Su, Tao-Hong; Cao, Jing; Li, Feng-Qin; Dong, Zi-Shu; Guo, Xin-Zhi; Zhang, Yan; Chen, Yang; Yang, Dong-Hua; Luo, Ping (Frontiers in Immunology, 2025)
G protein-coupled receptor 35 (GPR35), a member of the largest druggable gene family, has emerged as a critical regulator of tumor metabolism and immune modulation. Aberrant expression of GPR35 is frequently observed in digestive system malignancies and is associated with poor prognosis. This review comprehensively explores GPR35’s role in metabolic reprogramming, highlighting its regulatory functions in glucose, lipid, amino acid, and microbial metabolite metabolism. GPR35 shapes the tumor microenvironment through modulation of metabolite signaling, influencing angiogenesis, immune cell infiltration, and inflammation. It also acts as a key interface between host cells and the gut microbiota, contributing to cancer progression via microbial-derived metabolites. Pharmacological targeting of GPR35 shows promise, with several agonists and antagonists advancing through preclinical and early clinical development. However, challenges such as species-specific pharmacodynamics, ligand selectivity, and receptor isoform variability complicate drug development. Recent advances, including the creation of humanized GPR35 models, have facilitated translational research. Targeting GPR35-mediated metabolic reprogramming represents a novel therapeutic strategy, particularly for metabolically active digestive cancers. Future studies should focus on clarifying the metabolic pathways governed by GPR35 and optimizing receptor-specific therapeutics for clinical application.